PELATIHAN SELF HYPNOSIS EMPOWERMENT MENINGKATKAN EFIKASI DIRI PASIEN DIABETES MELLITUS - Manangkot, Meril Valentine; Suindrayasa, I Made (Coping: Community of Publishing in Nursing; Vol 11 No 3 (2023): Juni 2023DO - 10.24843/coping.2023.v11.i03.p15, 2023)
Diabetes mellitus is metabolic disorder characterized by increase in glucose concentration in the blood. DM treatment management lasts a lifetime, so it requires optimal self-efficacy. Self-efficacy can be realized by develop individual self-confidence, one way is by doing self-hypnosis empowerment. This study aims to determine the effect of self-hypnosis empowerment training on the self-efficacy of DM patients. The sampling technique used was consecutive sampling. Respondents consisted of 30 experimental group people and 30 control group people. The experimental group was given self-hypnosis empowerment training, while the control group only received general therapy. Data were collected using the Diabetes Management Sel-Efficacy Scale self-efficacy questionnaire. The results showed that there were differences in pre and post self-efficacy scores within the experimental group (p-value = 0,000), there were differences in pre- and post-self-efficacy scores within the control group (p-value = 0,000), and there were differences in self-efficacy scores between the groups experimental and control groups (p-value = 0,000). Health workers are expected to be able to provide education for DM patients to increase self-efficacy and motivation, in order to realize optimal health management behavior.